The involvement of ADAR1 in chronic unpredictable stress-induced cognitive impairment by targeting DARPP-32 with miR-874-3p in BALB/c mice - Wang, Yanfang; Liu, Yingxin; Zhao, Ziwei; Wu, Xinyu; Lin, Jiabin; Li, Yufei; Yan, Wei; Wu, Yi; Shi, Yanfei; Wu, Xindi; Xue, Ying; He, Jiaqian; et al. (Frontiers in Cell and Developmental Biology, 2023)
Chronic stress exposure is the main environmental inducement leading to cognitive impairment, but the detailed molecular mechanism is still unclear. Adenosine deaminase acting on double stranded RNA1 (ADAR1)　is involved in the occurrence of chronic stress-induced cognitive impairment. In addition, dopamine and adenosine 3'5'-monophosphate-regulated phospho-protein (DARPP-32) gene variation affects cognitive function. Therefore, we hypothesized that ADAR1 played a key role in chronic stress-induced cognitive impairment by acting on DARPP-32. In this study, postnatal 21-day male BALB/c mice were exposed to chronic unpredictable stressors. After that, the mice were treated with ADAR1 inducer/inhibitor. The cognitive ability and cerebral DARPP-32 protein expression of BALB/c mice were evaluated. The results demonstrate that ADAR1 inducer alleviates the cognitive impairment and recovers the decreased DARPP-32 protein expression of hippocampus and prefrontal cortex in the BALB/c mice with chronic unpredictable stress exposure. In order to explore the link between ADAR1 and DARPP-32, we detected the effects of ADAR1 high/low expression on DARPP-32 protein expression in vitro. The results confirm that ADAR1 affects DARPP-32 protein expression. In vivo and in vitro studies confirm the results predicted by bioinformatics, that is, ADAR1 affects　DARPP-32 expression　via miR-874-3p. The novel findings of this study provide a new theoretical basis for further revealing the molecular mechanism of chronic stress-induced cognitive impairment epigenetically.